The Reckoning : The Triumph of Order on the Texas Outlaw Frontier - Rose, Peter R. (Book collections on Project MUSE., 2012)
"The history of how order came to the Forks of the Llano River, the outlaw frontier of western Texas Hill Country. Provides insight into outlaw families as well as law officers and citizens who opposed them"--Provided by publisher.